TINGKAT LITERASI KEUANGAN MAHASISWA POLITEKNIK NEGERI AMBON - J VONNY LITAMAHUPUTTY (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study aims to determine level of financial literacy of students at Politeknik Negeri Ambon. Financial literacy is a fundamental thing that needs of individuals or communities in managing finances. Aspects of financial literacy used in this study are basic knowledge of personal finance, deposits and loans, insurance and investment. This research is a descriptive research conducted on active students at Politeknik Negeri Ambon in 2019-2020. The population is 3,091 active students. Sampling technique is purposive sampling. Data collection techniques are through the dissemination of research instruments in the form of questionnaires. While the data analysis techniques used are descriptive analysis. The results showed that the financial literacy rate of active students at Politeknik Negeri Ambon in 2020-2021 was 69.43 percent. The percentage is interpreted into the criteria of financial literacy level according to Chen and Volpe (1998) is in the moderate category.